Analysis of full resonance characteristics of underground magnetic coupling wireless power transfer system - ZHANG Lian; YANG Hongjie; JING Tingwei; LI Tao; ZHANG Lu (Gong-kuang zidonghua, 2022)
When the magnetic coupling wireless power transfer (MC-WPT) system is used for power supply underground, if the system parameters are not properly configured, the input impedance of the system will show non pure resistance, which will cause the system detuning and affect the power supply efficiency of underground power equipment. When the series compensation (S) is used in the secondary side of MC WPT system, it is easy to realize resonance. However, when the parallel compensation (P) is used in the secondary side, the existing research is based on the fact that the system only resonates at the primary side and the system does not fully resonate due to the non-resonance at the secondary side. In order to solve the above problems, a full resonance compensation method for magnetic coupling wireless power transfer (MC-WPT) system is proposed. In this paper, SP-type, PP-type, LCC-P type and LCL-P type compensation topologies are taken as the research object of the secondary side parallel MC-WPT system. The parameter constraint relation of the system in full resonance state is obtained by using impedance analysis method. The simulation comparison between the traditional compensation method and the full resonance compensation method is carry out by using Matlab/Simulink. The results show that the output power of SP type, PP type and LCL-P type compensation topology under the full resonance compensation method is greater than that under the traditional compensation method, and the output power of the LCC-P type compensation topology is less than that under the traditional compensation method. In the full resonance compensation method, the efficiency of SP-type and PP-type topology is not much different from that under the traditional compensation method, the LCC-P-type topology efficiency is much higher than that under the traditional compensation method, and the LCL-P-type topology efficiency is slightly lower than that under the traditional compensation method. In the full resonance method, the system does not need to provide reactive power, and the apparent power is equal to the given output power. In the full resonance compensation method, the SP topology is more suitable for underground coal mines, which is not affected by the change of mutual inductance, but is greatly affected by the resistance load. In order to solve the problem that the resonant frequency of SP Type MC WPT system is affected by the resistance load and the resistance load has a lower limit value under the full resonance compensation method, a DC-DC converter is used to combine impedance matching with active power factor correction. Therefore, the equivalent impedance of the input side of the rectifier bridge of the system is always equal to the corresponding resistance value of the preset resonant frequency. At the same time, it also ensures that the system rectifier bridge input current is in phase with the voltage, reducing the impact of the DC-DC converter introduction on the system impedance. The SP MC WPT system is taken as the experimental object for verification. The results show that the SP-type MC-WPT system can be free from the constraints of the resistance load in the full resonance compensation optimization method, the system is not affected by the mutual inductance and load changes, and is stable in the full resonance method, which improves the output power and output efficiency.